Parametric Model of Gyroscopes - Sotnik, S.; Ahmad M. Ayaz; Belova, N.; Lyashenko, V. (Scholars Academic and Scientific Publisher, 2018)
The classification of gyroscopes based on the parametric model is considered. It is shown that the proposed parametric model can be used as a basis for developing a mathematical model in the process of creating a module for the automated vibration gyroscopes design, mechanical or optical type. Investigations of the failure probability and the failure-free operation probability for a period of 50 hours to 150 hours and for a period of 200 hours to 400 hours were conducted. Parameters and graphical representation of computational models are given.
Keywords: Gyroscope; Construction; Parametric Model